(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the context of global climate change, it is possible to reduce CH4 gas by intensifying production and using resources efficiently. Also, in order to meet the growing needs of the population, increasing the volume of milk and dairy products, strengthening the feed base in livestock farming is one of the urgent issues. Also, in order to meet the growing needs of the population, increasing the volume of milk and dairy products, strengthening the feed base in livestock farming is one of the urgent issues. It should be noted that considering that 95% of the dairy products produced are consumed by households, one of the main objectives of the article is to study the processes of providing small-scale producers with feed and to develop scientifically based proposals.